Perkembangan Industri Keuangan Non-Bank Syariah dan Inovasi Service Excellent di Tengah Pandemi Covid-19 - Trimulato Trimulato (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
The purpose of this study was to determine development Sharia non-bank financial institutions (IKNB) during the COVID-19 pandemic as well as knowing form excellent service Sharia IKNB can do to meet the needs of customers or customers. Type of research is a literature study with a qualitative research nature. The source of the data used in this research is the data from the Financial Services Authority (OJK) and other data sources. Data collection techniques are form of documentation which is then processed by researchers. Data analysis technique used is descriptive qualitative. Results this study indicate development of Sharia IKNB in ​​period from October 2020 to April 2021, Sharia Insurance assets grew 6.26 percent, Pension Fund Institutions assets grew 17.79 percent, Sharia Microfinance Institutions assets grew 2.24 percent, Sharia Fintech Institution assets grew 85.54 percent. Meanwhile, Sharia Financing Institutions experienced a decrease in assets of -7.78 percent and Sharia Pawnshops experienced a decrease in assets of -6.95 percent. Excellent service Sharia IKNB can do during COVID-19 pandemic improving digital services, following applicable regulations, increasing attention and support for customers or customers, increasing partnerships with various parties.